Integrated Analysis of Metabolomics and Transcriptomics for Assessing Effects of Fish Meal and Fish Oil Replacement on the Metabolism of Rainbow Trout (Oncorhynchus mykiss) - Cao, Yiming; Gao, Qinfeng; Li, Xueqi; Zhou, Yangen; Dong, Shuanglin; Wang, Yinbo; Dai, Zhongyi (Frontiers in Marine Science, 2022)
Reducing dependency on dietary fish meal (FM) and fish oil (FO) is extremely important for the sustainable development of the aquaculture industry. However, the metabolic consequences and mechanisms underlying the replacement of dietary FM and FO by terrestrial proteins (TPs) and lipids remain unclear. To reveal the effects of replacing dietary FM and/or FO on the metabolic changes, the integrated analysis of metabolomics and transcriptomics were employed to evaluate the changes in metabolites and genes of rainbow trout (Oncorhynchus mykiss) feeding different experimental diets. Four diets were formulated for the 84-day duration of the experiment: control group (FMFO), FM and vegetable oil (FMVO), terrestrial protein and FO (TPFO), and terrestrial protein and vegetable oil (TPVO). Integrated metabolomic and transcriptomic analyses revealed the significant difference in the metabolic pathways of O. mykiss among the three replacement schemes, i.e., single replacement of dietary FM by TP, single replacement of dietary FO by VO, and combined replacement of FM by TP and FO by VO. The combined replacement of FM and FO by TP and VO, respectively, disturbed immune function, energy metabolism, cellular protein biosynthesis capacity, and lipid metabolism of O. mykiss. The reduction of antioxidant capacity was only observed in individuals feeding diets with replacement of FM by TP. Furthermore, as soon as the dietary FM and/or FO were reduced, cellular protein biosynthesis ability was suppressed and accompanied by higher energy consumption in response to fluctuations of dietary quality, resulting in reduced growth performance. Interestingly, adenylosuccinate and adenosine monophosphate involved in purine metabolism were induced by both individual and combined replacement of FM and FO by TPs and lipids, respectively. It suggested that these two metabolites might be potential biomarkers for O. mykiss fed diets with reduction of FM and/or FO. This study constitutes a new understanding of the molecular and metabolic mechanisms of O. mykiss in response to the replacement of dietary FM and/or FO by TP and/or VO, respectively, and built a theoretical basis for further improvement of aquafeed formulation and sustainable development of aquaculture.